Exploring Primary Healthcare Experiences and Interest in Mobile Technology Engagement Amongst an Urban Population Experiencing Barriers to Care - Pakhomova, Tatiana E; Nicholson, Valerie; Fischer, Matthew; Ferguson, Joanna; Moore, David M; Salters, Kate; Lester, Richard T; Kremer, Hayden; Dawydiuk, Nicole; Barrios, Rolando; Parashar, Surita (Qualitative health research, 2023)
Mobile phone-based engagement approaches provide potential platforms for improving access to primary healthcare (PHC) services for underserved populations. We held two focus groups (February 2020) with residents ( = 25) from a low-income urban neighbourhood (downtown Vancouver, Canada), to assess recent healthcare experiences and elicit interest in mobile phone-based healthcare engagement for underserved residents. Note-based analysis, guided by interpretative description, was used to explore emerging themes. Engagement in PHC was complicated by multiple, intersecting personal-level and socio-structural factors, and experiences of stigma and discrimination from care providers. Perceived inadequacy of PHC services and pervasive discrimination reported by participants indicate a significant and ongoing need to improve client-provider relationships to address unmet health needs. Mobile phone-based engagement was endorsed, highlighting phone ownership and client-provider text-messaging, facilitated by non-clinical staff such as peers, as helpful to strengthening retention and facilitating care team connection. Concerns raised included reliability, cost, and technology and language accessibility.